2015
DOI: 10.1002/ase.1590
|View full text |Cite
|
Sign up to set email alerts
|

An anatomy precourse enhances student learning in veterinary anatomy

Abstract: Veterinary anatomy is often a source of trepidation for many students. Currently professional veterinary programs, similar to medical curricula, within the United States have no admission requirements for anatomy as a prerequisite course. The purpose of the current study was to evaluate the impact of a week-long precourse in veterinary anatomy on both objective student performance and subjective student perceptions of the precourse educational methods. Incoming first year veterinary students in the Louisiana S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
2
28
0
3
Order By: Relevance
“…Medical students will likely continue to vary in pre‐existing anatomy knowledge, particularly in Canada, where anatomy courses are not a prerequisite for admission to any medical school (AFMC, ). As such, optional dissection during medical school or educational interventions prior to medical school, such as anatomy “boot camps” (Herling et al, ) or pre‐courses (McNulty et al, ), may reduce differences in anatomy preparedness that exist in students early in medical training.…”
Section: Discussionmentioning
confidence: 99%
“…Medical students will likely continue to vary in pre‐existing anatomy knowledge, particularly in Canada, where anatomy courses are not a prerequisite for admission to any medical school (AFMC, ). As such, optional dissection during medical school or educational interventions prior to medical school, such as anatomy “boot camps” (Herling et al, ) or pre‐courses (McNulty et al, ), may reduce differences in anatomy preparedness that exist in students early in medical training.…”
Section: Discussionmentioning
confidence: 99%
“…Student open responses were analyzed for common themes using axial and open coding that is based on Grounded Theory [41,42,43,44,45]. This retrospective process involved the extraction of one or more points of interest from each written comment, with subsequent independent placement into a topic theme by two researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Another study in an osteopathic medical program demonstrated a difference in gross anatomy performance favoring students who participated in the summer pre‐matriculation program on both block examinations and the final course grade (Herling et al, ). A veterinary school study (McNulty et al, ) demonstrated that students with summer pre‐matriculation coursework not only scored better on the repeated material in veterinary gross anatomy, but the gains also carried over to improved performance over non‐participating students on subsequent gross anatomy examinations. Tucker () demonstrated that not only can a pre‐matriculation course significantly predict performance in a medical gross anatomy course, but it also correlated to USMLE ® Step 1 examination scores.…”
Section: Introductionmentioning
confidence: 99%